Either/or. - Kierkegaard, Søren, 1813-1855 (Kierkegaard, Søren, 1813-1855. Works. 1978, 1987)
Søren Kierkegaard, the nineteenth-century Danish philosopher rediscovered in the twentieth century, is a major influence in contemporary philosophy, religion, and literature. He regarded Either/Or as the beginning of his authorship, although he had published two earlier works on Hans Christian Andersen and irony. The pseudonymous volumes of Either/Or are the writings of a young man (I) and of Judge William (II). The ironical young man's papers include a collection of sardonic aphorisms; essays on Mozart, modern drama, and boredom; and ""The Seducer's Diary."" The seeming misce